Enhancing Corporate Value Through Sustainability: The Role of Carbon Emission Disclosure, Green Accounting, and Environmental Performance in the Basic Materials Sector - Maushufi, Nadhira Nuril; Widoretno, Astrini Aning (Jurnal Akuntansi, 2025)
This study aims to analyze the influence of Carbon Emission Disclosure (CED), Green Accounting, and Environmental Performance on firm value, focusing on Basic Materials sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The method used is a quantitative approach with multiple linear regression analysis, and data processing was carried out using SPSS version 26. The results show that the three independent variables CED, Green Accounting, and Environmental Performance have a positive and significant effect on firm value. CED reflects corporate transparency on environmental issues, Green Accounting shows corporate responsibility in recording and reporting environmental costs, while Environmental Performance strengthens stakeholder trust. These findings confirm that the integration of environmental aspects into corporate strategy and reporting can increase firm value, especially in sectors with high emission intensity. The novelty of this study lies in its focus on the Basic Materials sector, which is still rarely studied in the context of environmental disclosure, and its approach that combines three environmental variables simultaneously. These results indicate that environmental responsibility is an important strategy in creating long-term value and sustainable competitiveness.